Agriculture as a Sector of Opportunity for Young People in Africa - Brooks, Karen; Zorya, Sergiy; Gautam, Amy; Goyal, Aparajita (World Bank, Washington, DC, 2013)
This paper sheds light on how to harvest the "youth dividend" in Sub-Saharan Africa by creating jobs in agriculture. The agriculture that attracts the youth will have to be profitable, competitive, and dynamic. These are the same characteristics needed for agriculture to deliver growth, to improve food security, and to preserve a fragile natural environment. With higher priority accorded to implementation of well-designed public investments in agriculture, continued progress on regulatory and policy reform, and attention to assure inclusion of young people in Africa's agricultural renaissance, the sector's handsome youth dividend can be collected and widely shared.